Linguistic features of comments by judges on tv programs: masterchef america and masterchef Vietnam - Đỗ Ngọc Minh Hà (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
It is widely acknowledged that language has been used for various purposes, one of which is performing actions. This study is designed to investigate the linguistic features of the judges’ comments on TV Program: MasterChef America and MasterChef Vietnam in 2013 and to find out similarities and differences between these comments’ features in the two languages. The study focused on analyzing linguistic features of CJs in terms of their pragmatic features, syntactic structures, and lexical choices. In order to pursue these objectives, the researcher combined different methods to examine 488 examples of judges’ comments through 45 episodes (25 episodes in MasterChef America and 20 episodes in MasterChef Vietnam) which were collected from English and Vietnamese TV shows and reuploaded by videos on Youtube (http://youtube.com). With regard to the pragmatic features, the findings of the study attempted to classify various intentions of the speaker in both English and Vietnamese. In terms of syntactic structures, the use of complete sentences, elliptical sentences and exclamatory sentences were the most striking structures in CJs. Dealing with the lexical choices, the study revealed that descriptive adjectives and adverbs and proper nouns are prominent in providing assessment of the dishes, the cooks’ performance as well as transmitting certain messages to the audiences effectively. Finally, the most significant aspect of the thesis is the similarities and differences between English comments by judges (ECJs) and Vietnamese comments by judges (VCJs). On the basis of the findings, some practical implications for teaching and learning English were suggested. Accordingly, it is hoped that this thesis can make theoretical and practical contributions to teaching and learning English and can be useful for those who are interested in reality TV shows.